On the Evolution and Appearance of a Surviving Companion after a Type Ia Supernova Explosion - Podsiadlowski, P (2003)
One promising method to test progenitor models for Type Ia supernovae is to identify surviving companion stars in historical supernova remnants. A surviving companion will have been strongly affected by its interaction with the supernova ejecta. Here we systematically explore the evolution and appearance of a typical companion star that has been stripped and heated by the supernova interaction during the post-impact re-equilibration phase. We show that, depending on the amount of heating and the amount of mass stripped by the impact or the previous binary mass transfer, such a star may be significantly overluminous or underluminous 10^3 - 10^4 yr after the supernova relative to its pre-supernova luminosity (by up to two orders of magnitude) and discuss the implications of these results for the strategies to be employed in searches for such companions.